Інформаційна система моделювання процесу реєстрації оптичного випромінювання - Стрілкова, Т. О.; Пятайкіна, М. І.; Дмитрук, С. С.; Пєвцова, М. О. (ХНУРЕ, 2025)
In this work, the development of an educational and research complex for studying the energetic, spatio-temporal, stochastic, and statistical properties of optical radiation is presented. The proposed information system for modeling the process of optical radiation registration includes modules for physical modeling, sensor registration, signal processing, and result visualization. The system is intended for scientific research, engineering development, and educational purposes, providing simulation, analysis, and optimization of processes related to the detection and processing of optical signals.
Keywords: фотодетектор; освітні цілі